Белый пароход: повести / Ч. Т. Айтматов - Айтматов Чингиз Торекулович (Школьная библиотека, 1981)
Экземпляры: (20220520) / Инвентарный номер: 1541 / Сис.шифр: 84(5Кир) / Авт.знак: А 36 / ББК: 84(5Кир)